Evaluasi Sistem Surveilans Demam Berdarah Dengue di Kota Tasikmalaya - Imas Masturoh; Ida Sugiarti; Muhammad Umar Riandi (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
Dengue Hemorrhagic Fever (DHF) has spread across all districts/cities in Indonesia, including in Tasikmalaya City as an endemic area. We conducted a mixed-methods study to evaluate surveillance system for dengue hemorrhagic fever in Tasikmalaya City. Qualitative data collection with in-depth interviews and focus group discussions. This research was conducted in the Tasikmalaya City Health Office’s work area from April to November 2018. Surveillance data through the hospital’s early warning report to the Tasikmalaya City Health Office mostly reported more than 24 hours. Completeness of reporting from RSU Dr. Soekarjo was 65.96% and TMC Hospital was 92%. There was a significant relationship between the presence of larvae and dengue cases (p-value = 0.001). It can be concluded that the accuracy and completeness of the hospital’s early warning report to the Tasikmalaya City Health Office was still relatively low due to the implementation of information system have not been integrated, DHF surveillance officers at both hospitals and puskesmas had double duty, lack of surveillance socialization/training for officers, and the lack of strengthening of accurately reporting at the management level and across sectors.